Trade Unions : The logic of Collective Action ; The Economics of Trade Unions - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Trade Unions : The logic of Collective Action," by Colin Crouch. This article reviews the book, "The Economics of Trade Unions," by Albert Rees.